2019
DOI: 10.1021/acsami.8b18232
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of Abrasive, Hard, and Thermally Conductive Synthetic Microdiamond–Polymer Composite Using Low-Cost Fused Deposition Modeling Printer

Abstract: A relative lack of printable materials with tailored functional properties limits the applicability of three-dimensional (3D) printing. In this work, a diamond−acrylonitrile butadiene styrene (ABS) composite filament for use in 3D printing was created through incorporation of high-pressure and hightemperature (HPHT) synthetic microdiamonds as a filler. Homogenously distributed diamond composite filaments, containing either 37.5 or 60 wt % microdiamonds, were formed through preblending the diamond powder with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 59 publications
5
53
0
Order By: Relevance
“…Intraoral appliances in orthodontics are prescribed for long continuous periods of wear; consequently, improvements in surface wettability will lead to improvements in retention between oral mucosa and the intaglio surface [33]. In the present study, the surface features of the ND were observed to influence the features of the polymer surface, with markedly significant reductions in water contact angle observed for both the ND-and A-ND-nanocomposite groups, in agreement with the observations of a previous study and highlighting the influence of the hydrophilic nature of diamond [34]. The difference between the ND-and A-ND-incorporated groups, however, can be attributed to changes in the surface chemistry resulting from the addition of amino groups, which reduces the surface reactivity of the oxygenated outer shell compared to that of pure ND, as previously described [35].…”
Section: Discussionsupporting
confidence: 92%
“…Intraoral appliances in orthodontics are prescribed for long continuous periods of wear; consequently, improvements in surface wettability will lead to improvements in retention between oral mucosa and the intaglio surface [33]. In the present study, the surface features of the ND were observed to influence the features of the polymer surface, with markedly significant reductions in water contact angle observed for both the ND-and A-ND-nanocomposite groups, in agreement with the observations of a previous study and highlighting the influence of the hydrophilic nature of diamond [34]. The difference between the ND-and A-ND-incorporated groups, however, can be attributed to changes in the surface chemistry resulting from the addition of amino groups, which reduces the surface reactivity of the oxygenated outer shell compared to that of pure ND, as previously described [35].…”
Section: Discussionsupporting
confidence: 92%
“…FDM technology (Figure 1(c)) is a low cost, simple, high speed, and commonly used method to fabricate thermoplastic‐based scaffolds. Herein, filaments melt into the semiliquid state and then extruded layer‐by‐layer through the nozzle on the platform according to the 3D designed file 54 . Thus, the viscosity of the semi‐molten filament affects the final structure and its printability and accuracy 55 .…”
Section: Bioprinting As An Innovative Technology For Bone Regenerationmentioning
confidence: 99%
“…The 3D printed ABS composites with 35 wt% of BN showed an improvement on thermal conductivity of five‐fold and a modest increase in the flexural modulus compared to that of the pure ABS matrix. In addition, Waheed et al 22 prepared the thermally conductive microdiamond filled ABS composites using FDM method. The resultant composites showed the highest thermal conductivity of 0.94 W m −1 K −1 with 60 wt% of microdiamond loading.…”
Section: Introductionmentioning
confidence: 99%